Asymmetric Assembly of All‐Carbon Tertiary/Quaternary Nonadjacent Stereocenters through Organocatalytic Conjugate Addition of α‐Cyanoacetates to a Methacrylate Equivalent. Issue 38 (3rd August 2016) - Iriarte, Igor; Vera, Silvia; Badiola, Eider; Mielgo, Antonia; Oiarbide, Mikel; García, Jesús M.; Odriozola, José M.; Palomo, Claudio
Abstract: An efficient, highly diastereo‐ and enantioselective assembly of acyclic carbonyl fragments possessing nonadjacent all‐carbon tertiary/quaternary stereoarrays is reported based on a Brønsted base catalyzed Michael addition/α‐protonation sequence involving α‐cyanoacetates and 2, 4‐dimethyl‐4‐hydroxypenten‐3‐one as novel methacrylate equivalent. Abstract : Michael does it again ! 2, 4‐Dimethyl‐4‐hydroxypenten‐3‐one has been introduced as new methacrylate equivalent for the asymmetric construction of nonadjacent all carbon tertiary/quaternary stereocenters through the organocatalytic addition of α‐cyanoacetates (see scheme). Direct assembly of such stereoarrays with high enantio‐ and diastereoselectivity has remained elusive to date.